PENERAPAN METODE CERAMAH PLUS DALAM PEMBELAJARAN PAI SELAMA PANDEMI COVID-19 DI KELAS 5 SD N 02 SUNGAI RUMBAI KABUPATEN DHARMASRAYA SEMESTER GANJIL TAHUN AJARAN 2021-2022 - Ira Wahyuni; Junaidi; Iswantir M; Arifmiboy (Universitas Pahlawan Tuanku Tambusai, 2022)
This research was motivated by several problems that the authors found, including students finding it difficult to understand the learning given by the teacher, lack of interest and motivation of students in participating in the PAI learning process, some teachers were not creative in using learning methods and only used the lecture method after that they just left the task at work. LKS after explaining learning, the time / hours of direct lessons in class were reduced during the Covid-19 pandemic and the number of students in the class was reduced due to the Covid-19 pandemic. This study uses a qualitative descriptive research method in the form of field research (Field Research). The key informants in this study were the 5th grade PAI teacher at SD N 02 Sungai Rumbai and the supporting informants were the principal and 5th grade students at SD N 02 Sungai Rumbai. Data collection was done by interview, observation and documentation. The data that has been collected is reduced, presented and conclusions are drawn. Based on the results of the research the author did, it can be concluded that the 5th grade PAI teacher at SD N 02 Sungai Rumbai uses the lecture plus method which is adapted to the material to be taught. For material that does not contain many verses of the Qur'an and the practice pattern used is the lecture method plus questions and answers and assignments. As for the material that contains many verses and the practice of the caramah plus method pattern used is the lecture method plus questions and answers, demonstrations and assignments. Obstacles faced by PAI teachers to apply the lecture method in grade 5 SD N 02 Sungai Rumbai include the teacher having difficulty adjusting the learning time a little with enough learning material, the long distance between the first meeting and the next meeting makes it difficult for the teacher to connect the material at the next meeting, teachers cannot combine the lecture method with the discussion method because of limited learning time, limited physical interaction between teachers and students so that teachers are limited to providing encouragement or physical stimulus to students, there are still some students who have difficulty understanding learning and students are less focused in following the process learning. Keyword: Methods, Lectures Plus, Learning, Islamic Religious Education